First and Second Language Acquisition - Meisel, JuÌˆrgen M (Cambridge University Press, 2011)
This is an introduction to the study of the human Language Making Capacity. More accurately, it is a textbook presenting research questions and research results referring to specific manifestations of this capacity in monolingual and bilingual first language acquisition and child and adult second language acquisition. A more comprehensive treatment of this subject would have to address other aspects as well, for example, the genesis and change of languages, creolization and pidginization, language attrition and loss, impaired acquisition, and so forth; Includes bibliographical references and indexes (pages 270-294)